Utilização da macroalga Gracilaria birdiae na alimentação de cabras em lactação em região semiárida - Lima, Renata Nayhara de (Universidade Federal Rural do Semi-Árido, 2017)
The nutritional potential of seaweed as a food supplement for domestic animals has already been the subject of several researches over time, however, the characterization of macroalgae found in the Brazilian coast and its potential as part of the ruminant diet still has much to be explored. The objective of this work was to evaluate the effect of different levels of inclusion of the Gracilaria birdiae seaweed on the lactating goats diet, on the variables food intake, milk production and composition, ingestive behavior, serum parameters and physiological variables in semiarid equatorial environment. Eight Saanen goats (47.1 ± 5.8 kg body wheitgh) were distributed in two Latin squares (4 x 4). Four inclusion levels (0, 4, 8 and 12%) of Macroalga Gracilaria birdiae were tested on the natural matter of the concentrate. Dry matter intake of hay and concentrate were not influenced by gracilaria levels in the diet (P>0.05). Ethereal extract consumption had a linear effect, with a reduction in intake as a function of the addition of GB in the diet (P<0.05). The mineral matter intake increased linearly as a function of GB levels in the diet (P<0.05). Ingestive behavior, milk production and composition, and energetic and protein status of goats were not influenced by the addition of macroalgae in the diet (P>0.05). Respiratory frequency, rectal temperature and surface temperature had a significant effect due to the inclusion of macroalgae (P<0.05), suggesting that macroalgae Gracilaria birdiae can attenuate the effects of the high radiation rates faced by dairy goats in the environment equatorial. Gracilaria birdiae can be used as a component of the lactating Sannen goat diet without detriment to the consumption, milk production and energy and protein status of the animals, and also contributes to soften the deleterious effects of heat stress when the ambient temperature rises
Seaweed Gracilaria birdiae in diet of dairy goats in semiarid region
Keywords: Comportamento ingestivo; Estresse térmico; Produção de leite; Status energético; Energy status; Ingestive behavior; Milk production; Thermal stress; CIENCIAS AGRARIAS::MEDICINA VETERINARIA